2016
DOI: 10.1038/ncomms10778
|View full text |Cite
|
Sign up to set email alerts
|

Two-colour live-cell nanoscale imaging of intracellular targets

Abstract: Stimulated emission depletion (STED) nanoscopy allows observations of subcellular dynamics at the nanoscale. Applications have, however, been severely limited by the lack of a versatile STED-compatible two-colour labelling strategy for intracellular targets in living cells. Here we demonstrate a universal labelling method based on the organic, membrane-permeable dyes SiR and ATTO590 as Halo and SNAP substrates. SiR and ATTO590 constitute the first suitable dye pair for two-colour STED imaging in living cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
181
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(184 citation statements)
references
References 25 publications
1
181
0
2
Order By: Relevance
“…The advantages of this combination are most evident by comparing the images obtained when HMSiR is conjugated to an ER-resident protein 33 , such as Halo-Sec61β 11 , or to the lipid probe Cer-TCO (Supplementary Movie 6). Although the signal from Sec61β-HMSiR was initially 2.3-fold higher than that from Cer-HMSiR, it decayed far more rapidly (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of this combination are most evident by comparing the images obtained when HMSiR is conjugated to an ER-resident protein 33 , such as Halo-Sec61β 11 , or to the lipid probe Cer-TCO (Supplementary Movie 6). Although the signal from Sec61β-HMSiR was initially 2.3-fold higher than that from Cer-HMSiR, it decayed far more rapidly (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…( a ) SMS images of the ER in HeLa cells expressing the two ER markers KDELR-mEos3.2 37 (green) and Halo-Sec61β 11 and treated with HMSiR-CA (red). An enlarged view of the image within the yellow box is shown at right.…”
Section: Figurementioning
confidence: 99%
“…The microscope design is a variant of a STED system described in detail previously (Bottanelli et al, 2016). Imaging was performed with either a 100x UPlanSApo 1.4 NA oil immersion objective lens (Olympus, Japan) or a 100x UPlanSApo 1.35 NA silicone oil immersion objective lens (Olympus, Japan) over a region of 15 × 15 μm with square pixels of 14.6 nm (1024 × 1024 pixels).…”
Section: Methodsmentioning
confidence: 99%
“…" Bewersdorf and his colleagues demonstrated that the two tags can be used with organic dyes in living cells to achieve a resolution below 50 nm 5 -almost as precise as the 20-nm resolution of the original techniques, with the advantage that they combine the specificity and leanness of genetically encoded probes with the brightness of synthetic dyes.…”
Section: Lasting Longer Shining Strongermentioning
confidence: 99%